Research that matters: the impact of IFPRI's policy research - Garrett, James L. (International Food Policy Research Institute, 1999)
IFPRI commissioned a series of in-depth case studies to look at how research findings are communicated to and used by policymakers. The case studies show that policy research can promote action that improves the lives of the poor. And they demonstrate that research often recovers its costs many times over in fiscal savings alone, without even considering more important improvements in poverty, food insecurity, and malnutrition. Case studies include 6 Impact Assessment Discussion Papers: Suresh Babu's “Impact of Policy Research on Resource Allocation and Food Security: A Case Study of IFPRI’s Research in Bangladesh” - Curtis Farrar's “A Review of Food Subsidy Research at IFPRI” - Yassir Islam and James L. Garrett's “IFPRI and the Abolition of the Wheat Flour Ration Shops in Pakistan: A Case Study on Policy-making and the Use and Impact of Research” - Robert L. Paarlberg's “External Impact Assessment of IFPRI’s 2020 Vision for Food, Agriculture, and the Environment Initiative” - James G. Ryan's “Assessing the Impact of Rice Policy Changes in Viet Nam and the Contribution of Policy Research” - James G. Ryan's “Assessing the Impact of Policy Research and Capacity Building by IFPRI with Malawi.